Relações entre o comprometimento do trabalhador e as políticas de gestão organizacional em tempos atuais - Borro, Núria Priscila Valentini [UNESP]; Goulart Júnior, Edward [UNESP]; Lunardelli, Maria Cristina Frollini [UNESP]; Canêo, Luiz Carlos [UNESP] (My University, 2010)
The present scenario of the employment market, demands an increasing commitment from employees based on one’s potential to offer the often required skills for companies who desire to hold on to a competitive position in its business segment. Studies about the relationship between commitment and the management polices demonstrates that many organizations are still neglecting the importance of their intellectual resources by applying some measures which result in a dangerous psycho-social environment and a decrease in the employee’s commitment. However, some well established organizations, attentive to signs from the market, are showing evidence of strategically integrated policies that invest in strengthening the relationship with their employees.

O atual cenário do mercado de trabalho demanda cada vez mais comprometimento do trabalhador, tendo em vista o potencial deste último em oferecer o diferencial tão requisitado pelas empresas que pretendem se manter em uma posição competitiva frente este cenário. Ao estudar as relações entre o comprometimento e as políticas de gestão adotadas, constatou-se que muitas organizações ainda negligenciam a importância de seu capital intelectual ao empreenderem medidas cujas conseqüências configuram um ambiente psicossocial nocivo à saúde e ao comprometimento do trabalhador. Por outro lado, organizações em posições já consagradas e atentas aos sinais do mercado evidenciam políticas estrategicamente integradas que investem no fortalecimento de seu vínculo com o trabalhador.
Keywords: Employee’s commitment; Organizational culture; Organizational management policies; Comprometimento do trabalhador; Cultura organizacional; Políticas de gestão organizacional